Bilingualism as a risk factor for false reports of stuttering in the Early Childhood Longitudinal Study (ECLS-K:2011) - Gahl, Susanne (Frontiers in Psychology, 2023)
Introduction Bilingualism has historically been claimed to be a risk factor for developmental stuttering. The Early Childhood Longitudinal Study, Kindergarten Class of 2010-11 (ECLS-K:2011) ostensibly contains evidence to test that claim. Methods We analyze data from monolingual and bilingual children in Kindergarten through fifth grade in the ECLS-K:2011. Results and discussion The prevalence, male/female ratio, and onset and recovery of reported stuttering in the ECLS are inconsistent with widely-accepted clinical reports of stuttering. We argue that the reported figures may be misleading. We discuss some factors that may inflate the reported prevalence, including a lack of awareness of the difference between stuttering vs. normal disfluencies, and the informal usage of the word “stuttering” on the part of teachers and parents to describe typical disfluencies.